DUX4 Immunohistochemistry Is a Highly Sensitive and Specific Marker for CIC-DUX4 Fusion-positive Round Cell Tumor. (March 2017) - Siegele, Bradford; Roberts, Jon; Black, Jennifer O.; Rudzinski, Erin; Vargas, Sara O.; Galambos, Csaba
Abstract : The histologic differential diagnosis of pediatric and adult round cell tumors is vast and includes the recently recognized entity CIC-DUX4 fusion-positive round cell tumor. The diagnosis of CIC-DUX4 tumor can be suggested by light microscopic and immunohistochemical features, but currently, definitive diagnosis requires ancillary genetic testing such as conventional karyotyping, fluorescence in situ hybridization, or molecular methods. We sought to determine whether DUX4 expression would serve as a fusion-specific immunohistochemical marker distinguishing CIC-DUX4 tumor from potential histologic mimics. A cohort of CIC-DUX4 fusion-positive round cell tumors harboring t(4;19)(q35;q13) and t(10;19)(q26;q13) translocations was designed, with additional inclusion of a case with a translocation confirmed to involve the CIC gene without delineation of the partner. Round cell tumors with potentially overlapping histologic features were also collected. Staining with a monoclonal antibody raised against the C-terminus of the DUX4 protein was applied to all cases. DUX4 immunohistochemistry exhibited diffuse, crisp, strong nuclear staining in all CIC-DUX4 fusion-positive round cell tumors (5/5, 100% sensitivity), and exhibited negative staining in nuclei of all of the other tested round cell tumors, including 20 Ewing sarcomas, 1 Ewing-like sarcoma, 11 alveolar rhabdomyosarcomas, 9 embryonal rhabdomyosarcomas, 12 synovial sarcomas, 7 desmoplastic small round cell tumors, 3 malignant rhabdoid tumors, 9 neuroblastomas, and 4 clear cell sarcomas (0/76, 100% specificity). Thus, in our experience, DUX4 immunostaining distinguishes CIC-DUX4 tumors from other round cell mimics. We recommend its use when CIC-DUX4 fusion-positive round cell tumor enters the histologic differential diagnosis. Abstract : Supplemental Digital Content is available in the text.